Rapid palatal expansion: a comparison of two appliances - Rodrigues, Amanda do Prado (2012)
This study analyzed occlusal radiographs to compare the transverse changes produced in patients treated with rapid maxillary expansion using two types of appliances. The sample consisted of 31 children aged 7 to 10.6 years, of both genders, with posterior cross-bite. Fifteen children were treated with a tooth-borne expander and 16 were treated with a tooth-tissue-borne expander. Occlusal radiographs obtained at treatment onset and at the end of the retention period were digitized. The following variables were measured: intermolar distance (IMD), interapical distance (IApD), interbase distance (IBaD) and interarm distance (IArD). The results revealed increases in all measurements in both groups after rapid maxillary expansion. Comparison between groups revealed that the increases were greater in patients treated with the tooth-borne expander, except for the IArD measurement, which presented the same increase in both groups. Even though the IMD measurements differed between expanders, they were proportional to the activation of the appliances (IBaD). The increase in the IApD measurement was proportionally greater in the group treated with the tooth-borne expander (0.7:1.0) than in that treated with the tooth-tissue-borne expander (0.4:1.0). It was concluded that both appliances had similar effects, although the tooth-tissue-borne expander produced a lesser opening at the apical region of the incisors.